Pola Konsumsi Minuman Remaja Pada Masa Pandemi Di Kecamatan Ngimbang - Yasir Arrokhim, Richi; Chusnah, Miftachul; Qomariah, Umi Kulsum Nur (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research aims toto find out the description of the consumption pattern of adolescent drinks during the pandemic in the Ngimbang sub-districtandfind out what types of drinks are often consumed by teenagers during the pandemic in the Ngimbang sub-district. The benefits of this research are expected to provide insight, description, knowledge to the public as well as information about drinking consumption patterns in adolescents.The approach in this study uses a qualitative approach. Qualitative research is descriptive in nature and tends to use analysis with an inductive approach. Sampling was carried out by purposive sampling, the collection technique was by triangulation by distributing questionnaires directly to the respondents, the data analysis was inductive/qualitative in nature, and the research results were presented using tables of frequency and percentage proportions. The location of this research was carried out in Ngimbang District, Lamongan Regency. The research results show: 1)the average water consumption pattern of all respondents is 1,850 ml per day, when compared to the recommendations in research conducted by (Aprillia & Khomsan, 2014), the average of all respondents who consume water is still insufficient, teenage boys Boys have an average consumption of water higher than girls. 2) out of 40 respondents, 15.9% of respondents regularly consumed spiced drinks during the COVID-19 pandemic with a frequency of 1 time one day.